1988
DOI: 10.1177/014920638801400205
|View full text |Cite
|
Sign up to set email alerts
|

Management Education and Development: Current Issues and Emerging Trends

Abstract: Rapid changes have been occurring in the management education and development area, fueled by the callfor accountability, an increase in experiental techniques, the availability of educational technology, and a recognition of the needfor lifetime learning. This review recognizes some of these changes and trends and suggests implications for practitioners. Recent literature in the field is reviewed according to a three-part typology: content, experience, and assessment/feedback. Research gaps in the field are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 85 publications
4
50
0
Order By: Relevance
“…Meaning, managers must acquire the knowledge, skills, and abilities vital to enhance task performance (Day, 2000). Moreover, as leadership tends to correspond to group processes -wherein organizational members must work as a collectivemanagement processes are often individualistic, and regarded as position and organization specific (Day, 2000;Keys & Wolfe, 1998). Although managers share the same common objectives as leaders -achieving organizational goals and mission fulfillment -the premise of management being position specific implies that a manager's focus is only on immediate concerns, priorities, and select individuals, as opposed to the entire entity.…”
Section: The Need For Leadership Developmentmentioning
confidence: 99%
“…Meaning, managers must acquire the knowledge, skills, and abilities vital to enhance task performance (Day, 2000). Moreover, as leadership tends to correspond to group processes -wherein organizational members must work as a collectivemanagement processes are often individualistic, and regarded as position and organization specific (Day, 2000;Keys & Wolfe, 1998). Although managers share the same common objectives as leaders -achieving organizational goals and mission fulfillment -the premise of management being position specific implies that a manager's focus is only on immediate concerns, priorities, and select individuals, as opposed to the entire entity.…”
Section: The Need For Leadership Developmentmentioning
confidence: 99%
“…Learning opportunities arising from challenging job experiences increases and enhances managers" employability, competitive advantage, career development and learning intensity (Lowy, Kelleher &Finestone, 1986 andWick, 1989). Even researches by Berlew & Hall (1966), Hunt (1991), Wexley & Baldwin (1986) and Keys & Wolfe (1988), as in Van der Sluis (2000, p.75), have scientifically proved that there were links between learning opportunities and career outcomes. Van der Sluis (2000, p.75-77) on learning environment and career success have found that learning opportunities were predictive of: (i) "income" (Gerhart & Milkovich, 1992), (ii) an "objective job performance" (Tannenbaum, 1997), (iii) a "subjective job performance" (Weick, 1996), and (iv) a "perceived career development" (Tannenbaum, 1997).…”
Section: The Link Between Managerial Learning and Career Success Percmentioning
confidence: 99%
“…It enables groups of people to work together, solve problems and use their seen and unseen capacities to face challenges (Keys & Wolfe, 1988;Hooijberg, Bullis & Hunt, 1999). Literatures have widely reported the important stages of leadership development.…”
Section: Leadership Development and Continuous Learning "The Primary mentioning
confidence: 99%